Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to determine whether the function defined implicitly by: $$x^2 + y^2 = 9$$ is a solution of the differential equation: $$\frac{dy}{dx}= \frac{x}{y}.$$ Please explain each step in process. I would like to very much understand the solution.

share|cite|improve this question
up vote 8 down vote accepted

You don't actually have to solve the differential equation to verify that the given function is a solution. What you need to do is "plug in" the proposed solution into the differential equation and see if you get the right answer. If you do, then it's a solution. If you don't, then it's not a solution.

But this is not "really" a differential equation anyway. What you need to do is compute the derivative of $y$ with respect to $x$ using implicit differentiation.

To do that, just differentiate with respect to $x$ both sides of the equation, using the usual differentiation rules; but you must remember that $y$ is "really" a function of $x$, so that you should use the Chain Rule whenever you are differentiating an expression involving $y$. Since you don't know what $y'$ is explicitly, you leave it indicated.

Once you are done, you "solve for $y'$".

Let me do a different example so you can see how it is done. Suppose you want to find $\frac{dy}{dx}$ for the function defined implicitly by $$x^3+y^3 = 3xy.$$ (The folium of Descartes) First, we take derivatives on both sides, remembering to use the Chain Rule; I'll do each term separately: $$\begin{align*} x^3 + y^3 &= 3xy\\ \frac{d}{dx}\left( x^3+y^3\right) &= \frac{d}{dx}3xy\\ \frac{d}{dx}x^3 + \frac{d}{dx}y^3 &= \frac{d}{dx}3xy &&\text{(since }(f+g)'=f'+g'\text{)}\\ 3x^2 + \frac{d}{dx}y^3 &= \frac{d}{dx}3xy &&\text{(since }(x^3)'=3x^2\text{)}\\ 3x^2 + 3y^2\left(\frac{dy}{dx}\right) &= \frac{d}{dx}3xy &&\text{(using the Chain Rule)}\\ 3x^2 + 3y^2y' &= \frac{d}{dx}3xy &&\text{(we don't know what }\frac{dy}{dx}\text{ is, so leave indicated)}\\ 3x^2 + 3y^2y' &= 3\frac{d}{dx}(xy) &&\text{(since }(3f)' = 3f'\text{)}\\ 3x^2+3y^2y' &= 3\left( x'y + xy'\right) &&\text{(product rule)}\\ 3x^2 +3y^2y' &= 3(y+xy') &&\text{(since }x'=1\text{)}\\ 3x^2 + 3y^2y' &=3y + 3xy' \end{align*}$$ Now, solve for $y'$: $$\begin{align*} 3x^2 + 3y^2y' &= 3y+3xy'\\ 3y^2y' - 3xy' &= 3y - 3x^2\\ 3(y^2-x)y' &= 3(y-x^2)\\ y' &= \frac{3(y-x^2)}{3(y^2-x)}\\ y' &= \frac{y-x^2}{y^2-x}. \end{align*}$$ So for the Folium of Descartes, $\frac{dy}{dx} = \frac{y-x^2}{y^2-x}$.

That's what you need to do to see whether $\frac{dy}{dx}$ for the circle of radius $3$ and center at the origin is equal to $\frac{y}{x}$; but it will be much easier than the above, so if you can follow the derivation here, your problem should be a snap.

share|cite|improve this answer
Can you please expand on the following steps please. 3x^2 + 3y^2\left(\frac{dy}{dx}\right) &= \frac{d}{dx}3xy &&\text{(using the Chain Rule)}\\ when you use Chain rule, why do you leave the 3y^2\left(\frac{dy}{dx}\right) in this when you didn't do that for the first. – user10695 Jun 16 '11 at 21:55
@user10695: $y$ is really a function of $x$; if we write it as $f(x)$ (instead of $y$), then it becomes clearer. We have $\frac{d}{dx}(f(x))^2$; how is this done? By using the Chain Rule: $\frac{d}{dx}(f(x))^2 = 2(f(x))*f'(x)$. Since $y=f(x)$, then $f'(x) = y' = \frac{dy}{dx}$. In fact I did do it "for the first", it's just that in that case you get $\frac{dx}{dx}$, which equals $1$, and of course multiplying by $1$ is the same as doing nothing. – Arturo Magidin Jun 17 '11 at 3:08

Do you know implicit differentiation? You can differentiate using the chain rule giving $2x+2yy'=0$ and see if it satisfies $y'=\frac{x}{y}$

share|cite|improve this answer
Alas, I am too late and too redundant! – The Chaz 2.0 Jun 15 '11 at 5:02
When I took the derivative of $$x^2 + y^2 = 9$$ , I got $2x+2y =0$ instead. May I ask how you got your answer please? – user10695 Jun 15 '11 at 5:06
He used the chain rule, like he said! You could write, after differentiating both sides with respect to x, $2xx' + 2yy' = 0$, but keep in mind that $x' = \frac{dx}{dx} = 1$, so that's why it doesn't appear in his answer. – The Chaz 2.0 Jun 15 '11 at 5:08
@The Chaz: I was elsewhere at the time. You got it. Thanks. – Ross Millikan Jun 15 '11 at 5:10
You were probably beating me to the punch elsewhere! :) – The Chaz 2.0 Jun 15 '11 at 5:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.